Survey manual for tropical marine resources (Australian Institute of marine Sciemce, 1997)
Softcover. Contains detailed methods for assessing tropical marine resources (coral reefs, mangrove forests, seagrass beds, soft bottom communities). Most of these methods have already been accepted by the UNEP-IOC-WMO-IUCN Global Task Team on Coral Reefs, for application during the global monitoring programme